Extending services and enhancing systems: working together to manage increased numbers of referrals. Issue 2 (1st September 2011) - Sutherland, Jane; Midgley, Corinna
Abstract : Improving access to palliative care for all patients with life limiting illness has resulted in a significant increase in referrals to specialist palliative care services. Expanding services to keep pace with increasing demand and ensure that all referred patients have access to specialist advice and clinical assessment in a rapid and timely manner has posed a challenge and placed greater emphasis on the importance of prioritising referrals according to need. Extending services to cope with growing numbers of referrals has required innovative thinking and enhanced systems. Our service has seen a 24% increase in referrals over the last 3 years. As referrals have risen in number it has become increasingly necessary to look at referrals management and review our processing of them. Our key aim being to ensure that referrals are prioritised according to need and dealt with as quickly as possible. We reviewed our management of referrals in a number of stages using a variety of methods including process mapping, audit and focus group work. Methods were chosen based on the size, needs and processes within each department. The review exposed a number of gaps, bottlenecks and inequities. Finding solutions to our bottlenecks and to better manage referrals has been well supported by our use a standardised holistic assessment tool across the organisation. We use an organisationally adapted version of the Support Team Assessment Schedule -STAS (Higginson, 1989) to structure our assessment of patients against 30 factors across all required domains. We are now working creatively to expand our use of the tool to prioritise referrals and manage departmental waiting lists. Evaluation has shown that using STAS within clinical departments has enabled us to enhance our method of processing and prioritising referrals according to need and ensure that we are better placed to meet demand.